ANALYSIS OF PHYSICAL ASPECTS OF MEDAN TELADAN STADIUM RENOVATION - Dara Wisdianti (Journal of Engineering, Electrical and Informatics, 2022)
The feasibility study of the Renovation of the Medan City Exemplary Stadium is to obtain a Foundation of the Planning and Design Program regarding the Renovation of the Exemplary Stadium in the City of Medan that meets the community's need for football as a nationally viable sports facility. The Feasibility Study of the Medan City Exemplary Stadium uses quantitative descriptive research, while the data used are primary data and secondary data. The Feasibility Study Method of Exemplary Stadium Renovation Planning to explain the design requirements (design needs) and design determinants related to the planning and design of the Exemplary Football Stadium. The analysis carried out is the physical analysis of the Medan Exemplary Stadium. As a result of the feasibility study of the renovation of the Teladan Medan Stadium, the physical condition of the Teladan Medan Stadium, the existing facilities, and infrastructure have been damaged and some are no longer functioning. And based on existing infrastructure problems, the renovation plan for the Medan Exemplary Stadium is very feasible. .